Railway seat design for injury mitigation in crash scenario - Carvalho, Marta (2020)
A validated framework developed to analyse railway occupant safety is presented here. The inexistence of restraints and the larger distance between contact features for the railway cabin interior decreases the predictability on the kinematics of its occupants. Simulation results are evaluated considering the severity of the injuries, assessed and quantified using the relevant criteria. It was introduced a head padding that conducted to a reduction of the Head Injury Criterion (HIC) but worsening the value of neck-bending moment in extension (NBME). Finally, the multi-objective optimization procedures are applied to achieve a relevant reduction in injuries. With the implementation of a pad with 42 mm thickness and with a reduction of 8.2% of the backseat plate thickness, is obtained a 41% reduction of the HIC but at the cost of an increase of 49% of the NBME index, though this design allows keeping all injury indices below moderate threshold value.